Group analysis and conservation laws of an integrable Kadomtsev–Petviashvili equation - Wang, Gangwei; Wang, Qi; Chen, Yingwei (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, an integrable KP equation is studied using symmetry and conservation laws. First, on the basis of various cases of coefficients, we construct the infinitesimal generators. For the special case, we get the corresponding geometry vector fields, and then from known soliton solutions we derive new soliton solutions. In addition, the explicit power series solutions are derived. Lastly, nonlinear self-adjointness and conservation laws are constructed with symmetries.
Keywords: integrable KP equation; symmetry analysis; soliton solutions; nonlinear self-adjointness; conservation laws